Comparison of Hypnobreastfeeding with Endorphin Massage on Breast Milk Production in Breastfeeding Mothers in the Koncara Community Health Center Work Area in 2025 - Armiyanti; Ine Hermina; Widia Natalia (CV. Inara, 2026)
Suboptimal breast milk production remains a major obstacle to successful exclusive breastfeeding. One non-pharmacological approach to increasing breast milk production is through relaxation techniques, such as hypnobreastfeeding and endorphin massage, which stimulate the release of prolactin and oxytocin hormones. This study aims to analyze the comparative effectiveness of hypnobreastfeeding and endorphin massage on breast milk production in breastfeeding mothers in the Koncara Community Health Center (Puskesmas) working area in 2025. The study used a quasi-experimental design with a non-equivalent control group pretest-posttest design. The study sample consisted of 68 breastfeeding mothers divided into two intervention groups, each consisting of 34 respondents, with an intervention duration of 14 days. Data analysis showed that both interventions had a significant effect on increasing breast milk production. However, the Mann–Whitney test results showed no significant difference in effectiveness between the hypnobreastfeeding and endorphin massage groups (p=0.702; p>0.05). These findings indicate that both methods have comparable effectiveness in increasing breast milk production. Therefore, hypnobreastfeeding and endorphin massage can be recommended as non-pharmacological interventions that can be integrated into midwifery services, especially in efforts to support the success of exclusive breastfeeding at the Koncara Community Health Center.